Okręg (Obszar) Lwów Armii Krajowej .......... 11 - Dudek, Tomasz (Kresowi żołnierze Armii Krajowej: Historia – Polityka – Pamięć, 2024)
THE HOME ARMY LVIV DISTRICT This section discusses the history of the ZWZ-AK (The Home Army Union of Armed Struggle) in its Lviv district during World War Two. In this paper, the author attempted to showcase the operations of individual units of the Polish underground resistance organisation in the Lviv area which targeted the Soviets, the Germans, and the Ukrainians, as well as to reconstruct the staffing of the Lviv district structures. What is interesting is that the author did not ignore an important, yet little known issue of the Polish civilian self-defence organised against Ukrainian nationalists targeting the Polish population with criminal acts in the Lviv area. It was the Polish self-defence operatives who allowed large clusters of Polish population to survive. The author discussed the course of Operation Tempest and the attempted to reconstruct the underground resistance structures under the new occupational force, the Soviets. The structures concerned are both the “NIE” resistance organisation and the extra-territorial Lviv district of the WIN (Freedom and Independence Association) formed in the novel environment of the Recovered Territories (a.k.a. Regained Lands or Western Borderlands).